Teach yourself Chinese--how? The history of Chinese self-instruction manuals for English speakers, 1900-2010 - McLelland, Nicola (Chinese Language Teachers Association, 2015)
This paper examines the history of self-instructional manuals of (Mandarin) Chinese published in Britain between 1900 and 2010, one of the main ways of learning Chinese for most of the 20th century in Britain, when Chinese instruction was virtually non-existent in schools and barely available in adult education classes. It thus contributes to the history of the prolific but under-researched genre of teach-yourself language manuals. More importantly, it aims to promote critical reflection on the aims and means of teaching Chinese to Eng-lish-speaking learners today, by examining how the authors of such manuals tackled the task in the past. After an overview of the history of Chinese language learning in the UK, the article examines the differing approaches to teaching Chinese in these texts (particularly varied in the first half of the 20th century), with particular focus on pedagogical approaches to the spoken and written language, to the grammar of Mandarin Chinese (including claims made about Chinese grammar, terminology and concepts used, and the presentation of measure words), and to representing Chinese culture. The paper concludes with some thoughts on how knowledge of the past can inform critical reflection on current materials and practice in Chinese as a Foreign Language.